Simultaneous radical cystectomy and nephroureterectomy: A case series - Gavin G. Calpin; Steven M. Anderson; Mark Broe; Ijaz Cheema; Niall F. Davis; Dilly Little (Surgery in Practice and Science)
Introduction: Simultaneous radical cystectomy and nephroureterectomy (RCNU) is a complex procedure. Although performed infrequently, RCNU may be indicated in certain cases of multifocal high grade urothelial carcinoma (UC) or muscle-invasive bladder cancer (MIBC) with an obstructed and atrophic kidney. The aim of this study was to review the indications, operative approach and outcomes for patients undergoing RCNU in our institution. Methods: A single-centre, retrospective review was performed. Cases were identified by reviewing theatre logbooks. Chart reviews were conducted and clinicopathological outcomes were recorded and analysed. Results: Eight patients were identified between 2015–2024. All were male and had a mean age of 66.4 ± 4.7 years. All patients underwent RCNU with ileal conduit formation. The surgical approach for the nephroureterectomy was laparoscopic in four cases and open in the remaining four. The mean post-operative length of stay was 11.6 ± 1.75 days. All patients had high grade UC, seven patients had MIBC at presentation. Only two patients received neoadjuvant chemotherapy, one of whom achieved a complete pathological response. In total, 62.5% (n=5) had T3/4 disease while 50% (n=4) had node positive disease. Two patients had synchronous upper tract urothelial carcinoma (UTUC) on final histology. The remaining cases had chronically obstructed and atrophic kidneys. Incidental primary prostate cancer was found in 62.5% (n=5). The mean follow-up was 31.6 ± 7 months, during which time there were four recurrences with three patients dying from metastatic disease. The mean overall survival was 21.8 ± 11.8 months and the mean disease-free survival was 19.3 ± 12.3 months. Conclusion: The results from this study demonstrate that combined laparoscopic and open RCNU is an effective treatment for both panurothelial cancer and MIBC with severe upper tract dysfunction.